Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Koperasi Dan UKM Kabupaten Bogor (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The Bogor District Small and Medium Enterprise Cooperative Service will assist cooperatives and micro, small and medium enterprises in the Bogor district to meet licensing requirements and build their capacity. Facilitation of halal certification licensing, food safety counseling certification, digital and packaging training, and development of new entrepreneurs for micro, small and medium enterprises in Bogor Regency. To find out the influence of leadership style on employee performance at the Cooperative Office of Small and Medium Enterprises in Bogor Regency, and to find out the effect of the work environment on employee performance and to find out the influence of leadership style and work environment on employee performance at the Office of Cooperatives and Small and Medium Enterprises in Bogor Regency. This research is a causal associative research with a quantitative approach. The sample of this research is 77 employees. the sampling technique used random sampling, the data collection technique used primary data and the data analysis technique in this study used the SPSS 25 application. Based on the results of this study it shows that Leadership Style has a partial effect on Employee Performance, Work Environment has a partial effect on Employee Performance. Then Leadership Style and Work Environment together (simultaneously) have a significant influence on employee performance.